Accuracy of Prediction of Birth Weight by Fetal Ultrasound - Bajracharya, J; Shrestha, NS; Karki, C (Kathmandu University Medical Journal, 2013)
Background Accurate determination of fetal weight prior to delivery can have a significant bearing on the management decision in labour, thereby markedly improving perinatal outcome. Objective To determine the accuracy of prediction of birth weight by fetal ultrasound. Methods This is the retrospective observational hospital based study done at Kathmandu medical college teaching hospital, Sinamangal, Kathmandu from January 2010 to February 2012. Total 150 women with full term singleton pregnancy leading to live birth were included in this study. Prenatal fetal ultrasound database was reviewed for fetal weight estimation. Delivery records were reviewed for actual birth weight. Error in estimation was calculated. Results Our study showed that fetal ultrasound using Hadlock’s formula has error in estimation of fetal weight by about 290 gm ± 250 gm. In 40% of the cases, there is an error of estimation by more than 10% compared to actual weight. Conclusion Significant error was seen while estimating fetal weight by ultrasound. Depending only on the fetal ultrasound for the estimation of fetal weight can lead to unnecessary obstetrical intervention. It is thus necessary to correlate the ultrasound findings with clinical examination. Kathmandu University Medical Journal | Vol.10 | No. 2 | Issue 38 | Apr – June 2012 | Page 74-76 DOI: http://dx.doi.org/10.3126/kumj.v10i2.7349